The Role of Theological Pre-Marital Counselling in Preventing Interfaith Marriage: A Pastoral Case Study in Bekasi, Indonesia - Fereddy Siagian (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the role of pre-marital counselling based on Christian values in preventing interfaith marriage and shaping Christian families grounded in the unity of faith. The research employs a qualitative approach with data collected through participant observation at the Pentecostal Church of Mangseng, North Bekasi, and at Taruna Kristen AMC Bekasi. Semi-structured interviews were conducted with pastors, counsellors, and participants, while theological and pastoral literature studies were carried out to strengthen the empirical findings with a biblical and academic conceptual framework concerning Christian marriage. The findings reveal that pre-marital counselling plays a significant role in strengthening the spiritual, emotional, and moral preparedness of couples to build Christ-centered households. Moreover, the youth formation program conducted at Taruna Kristen AMC Bekasi proved effective as an early preventive strategy to instill awareness of the dangers of interfaith relationships. These findings affirm that pre-marital counselling functions not merely as a technical preparation for marriage but also as an intergenerational faith-education medium that nurtures spiritual resilience and moral commitment among Christians. The implications of this research indicate that churches need to develop pastoral formation models that are empathetic, dialogical, and contextually relevant, ensuring that pre-marital counselling remains effective amid globalization and shifting social values. The originality of this study lies in the integration of theological teaching, pastoral practice, and youth faith education as a comprehensive strategy for preventing interfaith marriage. Thus, this research contributes to strengthening pastoral theology and developing a relevant pre-marital counselling model for churches in Indonesia.